Harms, Wrongs, and Medical Moral Injury - Sloane, Andrew (Studies in Christian ethics, 2023)
In this article I explore the contribution of ethical analysis and theological reflection to understanding and responding to moral injury of healthcare workers in light of the COVID pandemic. I begin by critically appraising the relevance of moral injury for healthcare contexts, and suggest that the term ‘medical moral injury’ should be used to differentiate it from ‘military moral injury’. I briefly relate medical moral injury to other relevant phenomena, such as moral dilemmas, moral distress, and moral residue, arguing that moral injury in healthcare contexts might take chronic as well as acute forms. I suggest that agent regret might play an important role in understanding medical moral injury. The associated distinction between harms and wrongs, and so regret and remorse, help us identify different kinds of moral injury, and the distinct role that apology plays in each instance. Theological reflection on penitence, forgiveness, and lament also contributes to understanding and responding to potentially morally injurious events. I conclude that while psychological intervention plays an important role in medical moral injury, moral and theological perspectives provide both crucial lenses through which to understand these potentially injurious moral landscapes, and resources to assist healthcare workers in navigating them more safely.